Molecular Sexing of Southeast Asian Barn Owl, Tyto alba javanica, using Blood and Feather - Shakinah Ravindran; Wai Kan Woo; Safwan Saufi; Wan Nur Amni; Noor Hisham Hamid; Cik Mohd Rizuan Zainal Abidin; Intan Ishak; Ghows Azzam; Hasber Salim (Tropical Life Sciences Research, 2019)
Sexing of birds is important for ecology and evolutionary biology studies, as well as breeding and conservation programs especially for sexually monomorphic birds. As for barn owls, Tyto alba, confirmation of sex is important for conservation as well as introduction programs to control rodent pest populations. Molecular sexing of Southeast Asian subspecies, Tyto alba javanica was carried out using Polymerase Chain Reaction (PCR) amplification followed by 3% agarose gel electrophoresis. Primers P2/P8 and 2550F/2718R for the amplification of CHD gene (Chromo Helicase DNA-binding gene) were tested and both gave successful results. 2550F/2718R primer set gave better results as the gap between double bands was larger. DNA extracted from blood, whole diluted blood, and DNA extracted from feathers was used to molecularly sex owls. DNA extracted from feather gave the least effective results owing to contamination and low DNA concentration, while sexing owls using direct whole diluted blood provided a cost and time effective method. Sequencing of CHD gene from Tyto alba javanica showed 98% to 99% similarity in identity when compared to CHD gene of Tyto alba alba. Penentuan jantina burung adalah penting untuk tujuan kajian ekologi dan biologi evolusi, serta program pembiakan dan konservasi terutamanya bagi burung yang mempunyai ciri monomorfik. Bagi burung pungguk jelapang Tyto alba, pengesahan jantina adalah penting untuk konservasi serta program pengenalan bagi kawalan tikus perosak. Penentuan jantina secara molekular untuk subspesies Asia Tenggara, Tyto alba javanica, telah dijalankan menggunakan Reaksi Rantai Polimerase (PCR) diikuti 3% gel agaros elektroforesis. Primer P2/P8 and 2550F/2718R untuk amplifikasi gen CHD (Chromo Helicase DNA-binding gene) diuji dan kedua-dua set primer memberi keputusan yang berjaya. Set primer 2550F/2718R memberi hasil yang lebih baik kerana jurang di antara jalur berganda lebih terang. DNA yang diekstrak dari darah, darah yang dicairkan, serta DNA yang diekstrak dari bulu burung digunakan untuk menentukan jantina burung. DNA yang diekstrak dari bulu memberi keputusan yang kurang memuaskan akibat pencemaran serta kuantiti DNA yang rendah. Penentuan jantina menggunakan darah yang dicairkan merupakan kaedah yang menjimatkan kos serta masa. Penjujukan gen CHD dari Tyto alba javanica menunjukkan 98% hingga 99% kesamaan identiti bila dibandingkan gen CHD Tyto alba alba.